DETERMINASI KOMUNIKASI DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN BANK SYARIAH INDONESIA (BSI) TANGERANG RAYA - Aulia Nursantoso, Fitria Melinda; Maulana, Irwan (Islamic Banking & Economic Law Studies (I-BEST), 2023)
This research aims to find out how communication and organizational culture determine employee performance at Bank Syariah Indonesia (BSI) Tangerang Raya. This type of research is quantitative research using primary data. The population in this study was 600 people from the total number of employees at Bank Syariah Indonesia (BSI) Tangerang Raya. The method used in this research is the Outer Model which includes the Individual Item Reliability test, Discriminant Validity, and Realibility test, while the Inner Model includes the R-Squared (R2), Predictive Relevance (Q2) and Path Coefficient value tests. The results of the research show that organizational communication influences the performance of employees of Bank Syariah Indonesia (BSI) Tangerang Raya, while organizational culture does not have a significant impact on the performance of employees of Bank Syariah Indonesia (BSI) Tangerang Raya.